Bulk density, velocity, impedance, reflectivity and relative abundance of potassium for IODP Site 361-U1475 - Jens Gruetzner; Francisco Jose Jiménez-Espejo; Nambiyathodi Lathika; Gabriele Uenzelmann-Neben; Ian R Hall; Sidney R Hemming; Leah J LeVay; IODP Expedition 361 Scientists (PANGAEA, 2018)
Listed are edited, spliced, and in situ corrected data vs. various depth scales, the shipboard age scale and two-way-traveltime (TWT). The shipboard age model for Site U1475 was derived from time estimates based on a combination of major planktonic foraminifer, calcareous nanno-plankton, diatom, and paleomagnetic datums. K (wt.%) is derived from measurements of natural gamma radiation (NGR) according to De Vleeschouwer, D., Dunlea, A. G., Auer, G., Anderson, C. H., Brumsack, H., de Loach, A., et al. (2017). Quantifying K, U, and Th contents of marine sediments using shipboard natural gamma radiation spectra measured on DVJOIDESResolution. Geochemistry, Geophysics, Geosystems, 18(3), 1053-1064, doi:10.1002/2016GC006715. Description of the depth scales: The CSF-A scale (here DEPTH, sediment/rock) is specific to each hole of a site and combines the drilling depth below seafloor of the core top depth and the curated depth within a core after retrieval. The CSF-A depth scale is equivalent to the meters below seafloor (mbsf) scale known from, e.g., the Ocean Drilling Program (ODP). For the construction of the most representative single continuous sedimentary section, intervals from multiple holes need to be spliced together. This requires a common, composite depth scale (CCSF, formerly known as mcd) for a given IODP Site which is based on the correlation of coeval, laterally continuous features seen in the physical properties in all drilled holes (which will generally occur at different depths on the CSF-A depth scales for each hole). Once such correlative features (tie-points) were identified at Site U1475 the depth of individual cores was offset relative to CSF-A in that hole, resulting in the Composite Curated depth below Sea Floor (CCSF-A) depth scale (here Depth composite) for each hole. By combining selected intervals from Holes U1475B, C, E and F between the previously established tie points a complete stratigraphic section (splice) was constructed. The designated depth scale of the splice is the CCSF-D scale. CCSF-D applies only to intervals included in the splice and intervals not included in the primary splice retain the CCSF-A scale. The CCSF-A scale does not result in alignment of all coeval features because of the differing effects of coring-induced stretching and squeezing among cores, as well as sedimentological differences between holes. For our study it was desirable to map into the splice those intervals not included in the splice itself. We accomplished this by simultaneously comparing color reflectance (b*) and NGR for all holes with subsequent identification of correlative tie points at the highest possible resolution and linear adjustments of depths between ties. This adjusted depth is designated as the CCSF-C depth scale (here Depth composite revised), and to the extent that the correlations are accurate, the CCSF-C and CCSF-D scales are equivalent. CCSF-C and -D typically exceed the in situ depth (core depth below sea floor CSF-A) by ~10%. The growth rate of the CCSF-D depth scale, relative to CSF-A is on average 9.5% for all holes. Thus to correct for the depth offset a linear compression - Depth (m CCSF-B) = Depth (m CCSF-C)/1.095 - was applied to the entire depth so that the compressed core length was equal to the interval cored. The CCSF-B scale (here Depth composite corrected) hence indicates the in situ depth in meters below the seafloor (mbsf).
Supplement to: Gruetzner, J et al. (2019): A new seismic stratigraphy in the Indian-Atlantic Ocean gateway resembles major paleo-oceanographic changes of the last 7 Ma. Geochemistry, Geophysics, Geosystems, 20(1), 339-358, https://doi.org/10.1029/2018GC007668